PENTINGNYA KEPEMINPINAN DALAM ORGANISASI - Danang Nugroho; Reza Ferdiansyah; Shelly Nur Fajrianti Rahayu; Moch Shiddiq Hermaya Putra; Thaufan Alif Nur Yasin; Isa Noor Zhalifunnas (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Leadership plays a crucial role in providing inspiration and encouragement to team members to achieve the goals set by an organization. It involves efforts to guide, motivate, and foster harmonious collaboration to reach optimal performance in line with productivity targets. Leadership is not merely about titles or status, but rather about making an impact and inspiring change. A leader must understand that at its core, leadership is about people and leading with empathy, care, and service. Factors such as the availability of funds, the drive for collaboration, and mutual agreements also influence the success of effective leadership. Effective leadership is key to achieving an organization's vision, mission, and objectives. This involves various leadership approaches and styles, such as authoritative, democratic, and laissez-faire, which can affect the overall performance of the organization. Leadership approaches involve functions like instructing, consulting, participating, delegating, and controlling. A leader plays a significant role in creating and maintaining a positive social atmosphere and providing support in formulating rules and operational steps. In the context of an organization, leadership holds a primary role in initiating transformation, directing the course of the organization, and facing potential risks. The role of leadership is also reflected in how a leader interacts with team members, focusing on both tasks and relationship.